Oil Removal From Produced Water Using Natural Materials - Gulistan, Abdul Sami (2014)
A Master of Science thesis in Chemical Engineering by Abdul Sami Gulistan entitled, "Oil Removal From Produced Water Using Natural Materials," submitted in June 2014. Thesis advisor is Dr. Taleb Ibrahim and thesis co-advisor is Dr. Hussain Ahmed. Available are both soft and hard copies of the thesis.